Angiotensin-Converting Enzyme Gene Polymorphism in Patients with Coronary Artery Disease - V. Ramakrishnan (Journal of Advanced Laboratory Research in Biology, 2010)
Several genetic investigations have been attempted to elucidate the association of gene polymorphism of angiotensin-converting enzyme (ACE) in coronary artery disease. This study was conducted to investigate the role of gene polymorphism of ACE in patients with coronary artery disease. The study included fifty-six numbers of patients with atherosclerotic coronary artery disease where proven angiographically and fifty-six numbers of healthy individuals of sex matched as a control group. The patients and control group were subjected to routine investigations, assays like, serum cholesterol, triglycerides, high-density Lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C). Genomic DNA was extracted and analyzed for angiotensin-converting enzyme insertion/deletion polymorphism using polymerase chain reaction (PCR). When we compared the genotypes of patients with coronary artery disease and controls, it was observed that all three genotypes were not statistically different also no significant difference of alleles in ACE gene genotypes was found. Inpatient serum cholesterol, triglyceride and HDL-C (P <0.001, P <0.001 and P <0.001: respectively) showed a significant increase than the control group. In patients, LDL-C level was not more significant than controls. In the evaluated population, we conclude that the gene I/D polymorphism for ACE are not risk associated and may not be a useful marker for coronary artery disease.